PERAN PERDAGANGAN INTERNASIONAL DALAM MENINGKATKAN PEREKONOMIAN DI INDONESIA - Asryah Wulandari; Aprilliantoni, Aprilliantoni (Cahaya Ilmu Bangsa, 2025)
The role of international trade is very important in supporting the development of the Indonesian economy through export and import activities. This activity is not only to increase state revenue, but can also help create jobs, increase foreign exchange reserves, and reduce poverty levels. This study was conducted using qualitative and descriptive methods based on literature to evaluate the impact of international trade on economic growth in Indonesia. The results of the study revealed that exports made a positive contribution to GDP growth, while the effect of imports varied depending on the type of goods imported. In addition, the MSME sector also made an important contribution to increasing investment and economic equality through the creation of new jobs. With effective management, international trade can be a catalyst for national development that aims to reduce economic disparities and improve the welfare of society as a whole.